2021
DOI: 10.7759/cureus.20255
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metastasis and Involvement of Level IV and V in Oral Squamous Cell Carcinoma: A Systematic Review

Abstract: The occurrence of occult metastases in oral cavity squamous cell carcinoma (OSCC) to lower levels in the neck (levels IV and V) or development of skip metastases that bypass the upper neck levels (levels I to III) and go directly to level IV or V is common. This challenges the efficacy of conventional neck dissection approaches in the treatment of OSCC. Therefore, the decision to include lower levels cervical nodes during elective neck dissection of OSCC remains controversial.This systematic review was designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Feng et al analysed 637 patients with OSCC who were treated by different ND regimes and did not find skip metastases alone at level IV or V or any neck recurrence at level IV or V [ 32 ]. In this context, in a systematic review assessing the prevalence of level IV and/or V involvement or skip metastases in patients with clinically negative or positive necks and OSCC, the authors concluded that selective ND including levels I–III would be reasonable in selected patients with cN+ necks [ 33 ]. In our study, we observed that the majority of LNMs were situated at levels I–III and that there were no significant differences in OS or DFS with regard to the localization of LNM.…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al analysed 637 patients with OSCC who were treated by different ND regimes and did not find skip metastases alone at level IV or V or any neck recurrence at level IV or V [ 32 ]. In this context, in a systematic review assessing the prevalence of level IV and/or V involvement or skip metastases in patients with clinically negative or positive necks and OSCC, the authors concluded that selective ND including levels I–III would be reasonable in selected patients with cN+ necks [ 33 ]. In our study, we observed that the majority of LNMs were situated at levels I–III and that there were no significant differences in OS or DFS with regard to the localization of LNM.…”
Section: Discussionmentioning
confidence: 99%
“…OLP could also increase the risk of oral cancer [ 117 ], with a malignant transformation rate of about 1.4% [ 118 , 119 ]. However, OSCC can also have a “de novo” appearance without any previous alteration of the oral epithelium [ 120 ]; the detection delay has a negative impact on the survival rate and allows this very aggressive malignancy to produce metastases in distant organs, identified in approximately 50% of the patients at the moment of diagnosis [ 121 , 122 ]. Therefore, early detection of OSCC and the screening of all types of PMOLs become crucial in prevention and treatment outcomes [ 123 ].…”
Section: Difficulties Associated With the Early Diagnosis Of Osccmentioning
confidence: 99%
“…However, despite more diverse and more advanced treatment options, the 5-year overall survival (OS) rate of OSCC has remained at 50–60% in recent years [7] . Clinically OSCC can metastasize to cervical lymph nodes via lymphatic vessels, and the incidence of metastasis is up to 40%, which is an important prognostic factor affecting survival [8] . OSCC also has a high recurrence rate, and patients with late recurrence have a worse 5-year OS rate [9] .…”
Section: Introductionmentioning
confidence: 99%